Um estudo sobre a influência de defeitos de diferente natureza nas propriedades eletrônicas de nanotubos usando o método das ondas cilindricas linearizadas aumentadas - GOMES, Fernando Antonio Pinheiro (Universidade Federal do Pará, 2015)
The carbon and boron nitride nanotubes are one-dimensional structures which exhibit behavior both as metallic and semiconductor, depending on their chirality, except for the nanotubes of boron nitride which always have semiconductor characteristics, for pristine nanotubes. Due to their electronic characteristics, the nanotubes have great potential for application in nanoelectronic devices, such as nanodiodes, nanotransistors, interconnection elements, etc. For this reason, it is important to understand how external factors influence on the properties of such materials. One such factor is the introduction of external defects in the nanotubes. Such defects are the absence of one or more carbon atoms belonging to carbon nanotube and nitrogen or boron for boron nitride nanotubes, or the substitution of carbon, nitrogen or boron atoms by different ones in the structure of the corresponding nanotubes. This work presents a theoretical study of the effects of the introduction of a substitutional defects in the electronic properties of carbon and boron nitride nanotubes, via ab-initio simulation. The energy band and density of states structures was evaluated for both semiconducting and metallic carbon nanotube armchair and zig-zag types respectively and for boron nitride nanotube only armchair type using the method LACW - linearized augmented cylindrical waves. Furthermore, due to the boron nitride nanotubes are growing in importance, we make an additional systematic study of the electronic structure for these nanotubes, for a super cell formed by three unit cells, using intrinsic doping as well as quantitative analysis about relative stability based on the total energy and band gap value of these structures.